Effect of standard and physiological cell culture temperatures on in vitro proliferation and differentiation of primary broiler chicken pectoralis major muscle satellite cells - Gregg, Caroline R.; Hutson, Brittany L.; Flees, Joshua J.; Starkey, Charles W.; Starkey, Jessica D. (Frontiers in Physiology, 2023)
Culture temperatures for broiler chicken cells are largely based on those optimized for mammalian species although normal broiler body temperature is typically more than 3 °C higher. The objective was to evaluate the effects of simulating broiler peripheral muscle temperature, 41 °C, compared with standard temperature, 38 °C, on the in vitro proliferation and differentiation of primary muscle-specific stem cells (satellite cells; SC) from the Pectoralis major (PM) of broiler chickens. Primary SC cultures were isolated from the PM of 18-day-old Ross 708 × Yield Plus male broilers. SC were plated in triplicate, 1.8-cm2, gelatin-coated wells at 40,000 cells per well. Parallel plates were cultured at either 38 or 41 °C in separate incubators. At 48, 72, and 96 h post-plating, culture wells were fixed and immunofluorescence stained to determine expression of the myogenic regulatory factors Pax7 and MyoD as well as evaluated for apoptosis using a TUNEL assay. After 168 h in culture, plates were immunofluorescence stained to visualize myosin heavy chain and Pax7 expression and determine myotube characteristics and SC fusion. Population doubling times were not impacted by temperature (P ≥ 0.1148), but culturing broiler SC at 41 °C for 96 h promoted a more rapid progression through myogenesis while 38 °C maintained primitive populations (P ≤ 0.0029). The proportion of apoptotic cells increased in primary SC cultured at 41 °C (P ≤ 0.0273). Culturing at 41 °C appeared to negatively impact fusion percentage (P < 0.0001) and tended to result in the formation of thinner myotubes (P = 0.061) without impacting the density of differentiated cells (P = 0.7551). These results indicate culture temperature alters primary broiler PM SC myogenic kinetics and has important implications for future in vitro work as well as improving our understanding of how thermal manipulation can alter myogenesis patterns during broiler embryonic and post-hatch muscle growth.